A study of the classification of the mandibular arch forms in a Filipino sample population using the MBT appliance - Zhang, Zebiao
The achievement of a stable, functional, and esthetic arch form has long been one of the prime objectives of orthodontics. A key aspect in the achievement of this goal was the identification of a suitable arch form to use in the treatment of each case. For over a century, researchers have been trying to define the "ideal" arch form, and various solutions to this problem have been proposed, but few have stood the test of time. More recently, with the advancements in the preadjusted appliance systems, the application of the MBT(with TM superscript) pre-selected arch form guides have made it easier and less time consuming to do some minor modifications associated with individual variations in the human arch form. The Filipino sample was examined to determine whether a particular MBT arch form type (tapered, ovoid, square) could be identified and conform to a specific type of Angle's malocclusion. A total of a hundred and five mandibular casts of Filipino adults were classified as Class I with N=35, Class II with N=35 and Class III with N=35 malocclusion groups.Four linear measurements of the mandibular dental arches were performed and two independent ratios were determined. A TESA Digit-Cal caliper was used to measure the photocopied images of the study casts to the nearest 0.001 mm accuracy.
Clinical bracket points were calculated for each tooth based on mandibular tooth thickness data. All data obtained from the six (6) measurements on each model were subjected to statistical analysis. The results of the DMRT (Duncan's Multiple Range Test) was used to assess the mean values of the various parameters in all Angle's malocclusion groups, as well as the arch from types, among the different ethnic groups. The result showed the following: firstly, that the square arch from was more predominant in the Filipino sample than in the tapered or ovoid arch forms; secondly, that there were no significatn differences in the distribution of the three arch forms accoding to sex; thirdly, that the Filipino male sample showed a wider arch compared to the female sample; fourthly, that the Filipino sample had a narrower arch in all Angle's classifications compared to the Japanese group, but the Filipino sample had wider posterior arch that the Korean goup in Class III cases and wider anterior arch compared to the Caucasian group in Class II cases and a wider anterior arch compared to the Caucasian group in class II cases
fifthly, that racial differences were established from the comparison of the arch dimensions among the ethnic groups, when regrouped according to the arch form types; and lastly, no specific arch form characterized any of the Angle classification or ethnic groups.
TM superscript after MBT on title.
Thesis (Master of Science in Dentistry)--University of the Philippines Manila
Keywords: Orthodontics; Dental arch